2012
DOI: 10.1063/1.4733952
|View full text |Cite
|
Sign up to set email alerts
|

Study of the photoluminescence emission line at 3.33 eV in ZnO films

Abstract: We study properties of the line at 3.33 eV observed in photoluminescence (PL) emission spectra of various ZnO films prepared using pulsed laser deposition method. The influence of deposition parameters, such as oxygen pressure, laser fluence, post-annealing, and electric field exposure on intensity of this luminescence band has been investigated. The recombination characteristics are probed by temperature and excitation dependent PL spectroscopy. The obtained experimental data suggest that the 3.33 eV luminesc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 54 publications
2
22
0
Order By: Relevance
“…This transition line at 3.33 eV was previously observed in various ZnO samples and tentatively ascribed to donor bound excitons (DX), acceptor bound excitons, transitions of intrinsic point defects and excitons bound to extended structural defects. The most detail study of this transition was reported by Yalishev et al [12] and Wagner et al [3]. In their work, the 3.33 eV emission line was attributed to recombination of excitons bound to extended structural donor defect complexes which disappear at temperature of 10 K. Study done by Urgessa et al [26] on ZnO nanorods growth for temperature dependent PL also observe dominance of donor-bound exciton as possible reason for this emission.…”
Section: Temperature Dependent Plmentioning
confidence: 81%
See 1 more Smart Citation
“…This transition line at 3.33 eV was previously observed in various ZnO samples and tentatively ascribed to donor bound excitons (DX), acceptor bound excitons, transitions of intrinsic point defects and excitons bound to extended structural defects. The most detail study of this transition was reported by Yalishev et al [12] and Wagner et al [3]. In their work, the 3.33 eV emission line was attributed to recombination of excitons bound to extended structural donor defect complexes which disappear at temperature of 10 K. Study done by Urgessa et al [26] on ZnO nanorods growth for temperature dependent PL also observe dominance of donor-bound exciton as possible reason for this emission.…”
Section: Temperature Dependent Plmentioning
confidence: 81%
“…The UV emission is due to excitonic related recombination [7,8]. The exact mechanism for deep level emission is still controversial although intrinsic defects such as oxygen vacancies, oxygen interstitial, zinc vacancies and extrinsic impurities are all considered as a possible origin [9][10][11][12]. However, understanding the origin of photoluminescence in ZnO nanoparticles and improving the emission efficiency is still a major challenge.…”
Section: Introductionmentioning
confidence: 98%
“…A broad peak centered at 3.33 eV at 10 K can be can be ascribed to a bound exciton (BE) complex located near the surface and grain boundaries. The probable corresponding defects are suggested (Yalishev et al, 2012). We observed optical phonon (LO) replicas of recombination of bound excitons, 1LO at 3.26 eV, 2LO at 3.19 eV and 3LO at 3.12 eV eV, which suggests strong coupling with phonons.…”
Section: Resultsmentioning
confidence: 66%
“…5(c) plots the integrated intensities of LBX as a function of reciprocal temperature. The temperature dependence of LBX intensity can be expressed by the following Arrhenius equation [21]:…”
Section: Resultsmentioning
confidence: 99%